147 Handling and disposal of agricultural chemicals on a2 farms in chirumhanzu district.32nd Triennial Congress of the International Commission on Occupational Health (ICOH), Dublin, Ireland, 29th April to 4th May 2018 - Matunhu Viola (BMJ Publishing Group, 2023)
In 2000 the Government of Zimbabwe undertook a massive land redistribution programme under its black economic empowerment policy where white-owned farms were seized and sub-dividing into smaller A1 and A2 models and redistributed to landless black majority. However, most of the land beneficiaries were ill-resourced and ill-trained to use the land in an ecologically friendly manner. This paper investigated how newly resettled farmers handled and disposed agricultural chemicals on the acquired A2 farms. In-depth interviews and observation where the main data collection instruments. The study involved farm employees on A2 farms that use agro-chemicals to enhance farm productivity. A total of 150 respondents participated in the study. The findings of this study indicated that despite the availability of statutory provisions on handling and disposal of agricultural chemicals, there is rampant mismanagement of environmentally unfriendly chemicals on the farms. Although most of the employees on the farms are literate, they find it difficult to understand the technical jargon used on these chemical labels. The study also established that agricultural chemicals are vital in sustaining Zimbabwe’s agricultural sector in terms of food security, foreign exchange generation, employment and provision of raw material for the manufacturing sector. On the other hand mismanagement of these chemicals can have adverse effects on human beings and the environment. It is therefore, important for farmers and their employees to be trained on personal, public health and environmental implications of poor management of agricultural chemicals. The paper recommends that the Zimbabwean Government should adopt a multi-sectoral campaigns strategy against mismanagement of agricultural chemicals. Use of electronic and print media of communication through the local languages is also recommended.